At Europe's service the origins and evolution of the European people's party - Jansen, Thomas (Springer, 2011)
The European people's party, the largest political party in Europe, has roots that run deep in history. Founded in 1976 as a Christian Democratic federation, the European People's Party is now a strong centre-right movement and a leading European political family. It has member parties in almost all European countries, and it is very well represented in the institutions of the European Union. This book tells the story of the European People's Party: why it was founded, how it is currently organised and what its guiding ideas, values and principles are. It gives an up-to-date account of the party's contribution to European integration, its work with its member parties and its central role in organising the centre-right in Europe. Above all, this book is for everyone who wants to know what a European-level political party looks like, how it is structured and how it acts.